Dynamic Analysis of Major Components in the Different Developmental Stages of Tenebrio molitor - Yu, Xiao; He, Qiang; Wang, Dun (Frontiers in Nutrition, 2021)
The yellow mealworm, Tenebrio molitor, is an important resource insect with a high protein percentage that is widely farmed in many countries. In this study, the content dynamics for protein, fat, chitin, and other components in the whole development process of yellow mealworms were analyzed by sampling from different instars and combining with their growth conditions. The results of the component dynamic analyses in the different development stages showed that the percentages of protein, fat, and chitin were the highest in the larval stage, pupal stage, and adult stage, respectively. The results of amino acid composition dynamic analysis also indicated comparatively higher essential amino acids in the earlier instar (e.g., before the 9th instar) larvae. Therefore, we found that the earlier instar is better than the final instar as the insect farming harvest time. Furthermore, the larvae in the earlier instar consumed dramatically less feed and could effectively reduce the farming costs of insect farmers. This finding provides an alternative option to farm insects for different purposes and in an economic way.